Solve the system :

3x+4y=-3

x+2y=-5

We can solve using the combinations method:

Multiply the second equation by -2, then add the resulting equation to the first equation:

3x+4y=-3

-2x-4y=10

------------

x=7

Substituting x=7 into the first equation we get:

3(7)+4y=-3

4y=-24

y=-6

-----------------------------------------------------------------

The solution is (7,-6)

------------------------------------------------------------------

Check: 3(7)+4(-6)=21-24=-3 and 7+2(-6)=7-12=-5

The graphs:

The system of equations 3x+4y=-3 and x+2y=-5 has to be solved.

From the equation x+2y=-5, express x in terms of y.

x+2y=-5

x = -5 - 2y

Now substitute this for x in 3x+4y=-3

3*(-5 - 2y) + 4y = -3

-15 - 6y + 4y = -3

-2y = 12

y = -6

x = -5 - 2y = -5 - (-6*2) = -5 + 12 = 7

The solution of the given system of equations is x = 7 and y = -6